Influence of implant macrodesign and insertion load during implant placement on primary stability in artificial bone - Yiwen Wang; Yoko Yamaguchi; Poyuan Hsueh; Daisuke Higuchi (International Journal of Implant Dentistry)
Abstract Background Implant placement is a critical step for achieving primary stability. During this process, a compressive force, referred to as an “insertion load,” is applied through a handpiece or manual driver. However, the influence of the insertion load has not been quantitatively investigated. Since primary stability is essential for predicting successful osseointegration, clarifying the effects of the insertion load may contribute to improving the safety and success of implant treatment. Methods Straight single-thread implants with pitches of 0.6 mm (S06) and 1.2 mm (S12) and double-thread implants with a 0.6 mm pitch (D06) were used (10 each). Insertion loads of the minimum required load, 5 N, 10 N, and 15 N were applied. Insertion torque values (ITVs), removal torque values (RTVs), and insertion times were measured (p = 0.05). The interface between the implants and the simulated bone was observed with a digital microscope under each load. Results The minimum insertion load was greatest in the order of S12 < S06 < D06. Variation in the insertion load did not affect the ITV or RTV, but lower loads extended the insertion time. Increased insertion loads led to more voids caused by bone fragment loss, especially in the double-thread designs. Conclusions While the insertion load did not directly influence the ITV or RTV, it varied by implant design. Higher loads potentially damage the surrounding bone, indicating the importance of careful load management.